Virtual try-on and analysis of haenyeo suits using digital technology - Eom, Rani (Edelweiss Applied Science and Technology, 2025)
This study aims to digitize information about Korean haenyeo suits and reveal their characteristics and current status to preserve the culture of Jeju haenyeo in South Korea. We created an avatar of a woman in her 60s—the typical wearer of haenyeo suits—measured the physical properties of the haenyeo suit fabric, generated patterns reflecting these properties, and conducted virtual try-on simulations. After analyzing haenyeo suits according to the morphological criteria of shape, dimensions, and clothing pressure, this study identified the following regarding their characteristics and current status. A haenyeo suit has activeness to facilitate the movements of a haenyeo during work and protectiveness to prevent seawater from entering. At a time when the number of haenyeo suit manufacturers is continuously decreasing, the pattern dimensions of the suits must be standardized. Moreover, a haenyeo suit has patterns that closely fit the wearer’s body. Hopefully, this study will inspire further research on the haenyeo culture.